Effects of penicillin and montelukast sodium on middle ear mucosa in rats with experimental acute otitis media - Uçar Topalsan, Seçil; Huseynov, Tural; Sarıoğlu, Sülen; Şerbetçioğlu, Bülent (ENT Updates, 2012)
Objective: To develop an experimental acute suppurative otitis media model and compare the responses of rats to penicillin and combinations of leukotriene antagonist with respect to histopathological observations conducted at both early and late phases. Methods: A total of eighty-three ears from fifty six Wistar rats used in this study. Pneumococcus suspension was injected transtympanically to all the rats. Subjects were classified under four different groups having 14 rats at each. In Group A, intramuscular penicillin G was injected to rats for a period of five days. In Group B, intraperitoneal montelukast was injected for 21 days in addition to penicillin. In Group C, intraperitoneal montelukast and in Group D intraperitoneal isotonic NaCl was injected to rats for 21 days. Cross-sections were semi-quantitatively graded with respect to various inflammatory components. Results: No significant difference was found between the groups, apart from mucosal vascularization with respect to mucosal and tympanic membrane (TM) parameters at early phases. However, statistically significant differences were found for the improvement of TM thickness with the help of penicillin treatment. Furthermore, considerable deviations were observed for the recuperation of TM and mucosal inflammation for groups where subjects were injected with montekulast as compared to other groups of the study. Conclusion: The results of this study clearly show that the beneficial effects of the antibiotic (penicillin) as well as leukotriene antagonist (montelukast) is statistically different those of placebo in acute otitis media in rats. When the parameters of inflammation in the rat middle ear were compared with each other, most of these parameters did not show any statistically different beneficial effects in montelukast and penicillin groups.